Nominal shocks and current account dynamics: A structural VAR analysis in the Southeast Asian countries - Sek, Siok Kun (2007)
This paper investigates empirically the roles of nominal shocks in determining the fluctuations of current account in four financial crisis hit countries in Asia. Structural VAR models are estimated separately for these economies before and during/after the financial crisis of 1997. The results show that the relative roles played by nominal shocks vary between two periods and across countries. This implies that the determinants of the current account fluctuations are relied on country-specific particularities. Trade openness does not show a significant contribution in explaining these differences.